Dryland soils in northern China sequester carbon during the early 2000s warming hiatus period. (30th March 2018) - Kou, Dan; Ma, Wenhong; Ding, Jinzhi; Zhang, Beibei; Fang, Kai; Hu, Huifeng; Yu, Jianchun; Wang, Tian; Qin, Shuqi; Zhao, Xia; Fang, Jingyun; Yang, Yuanhe
Abstract: Drylands, covering c . 45% of the Earth's terrestrial surface and supporting c . 38% of the global population, play a dominant role in the trend and interannual variability of global land carbon (C) sink. Given that a large proportion of organic C is stored in soils, our knowledge on soil C dynamics in drylands is crucial to evaluate terrestrial C‐climate feedback. However, credible understanding on this issue is still greatly limited by the lack of direct observations. Here, based on a regional resampling of historical sites collected during 2002–2004, we explored the soil organic C (SOC) changes in various layers over the past decade across the arid/semi‐arid grasslands on the Inner Mongolian Plateau. Our results revealed that the SOC density in this typical dryland increased significantly over the monitoring period, with a mean increase in 50.6 g C m −2  year −1 or 0.8% per year in the top 50 cm depth. Moreover, soil C dynamics exhibited contrasting spatial patterns between different layers: the rate of C accumulation in surface soils (0–10 cm) decreased, whereas that in deep soils (30–50 cm) exhibited an increasing trend along the aridity gradient. Collectively, these findings demonstrate that dryland soils function as an important C sink, with the drier region tending to sequester C in deeper soils due to the greater root biomass allocation. A plain language summary is available for this article. Abstract : Plain Language Summary